2005
DOI: 10.1248/bpb.28.1919
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lipopolysaccharide-Induced Expression of Inducible Nitric Oxide and Cyclooxygenase-2 by Chiisanoside via Suppression of Nuclear Factor-.KAPPA.B Activation in RAW 264.7 Macrophage Cells

Abstract: The plants belonging to Acanthopanax species (Araliaceae) are traditionally used in Korea as anti-rheumatoid arthritis, anti-inflammatory and anti-diabetic drugs and are recognized to have ginseng-like activities.1,2) 3,4-Secolupanetype triterpenoid family members, such as chiisanoside, chiisanogenin, 22-hydroxychiisanogenin, 24-hydroxychiisanogenin, etc. have been previously isolated from Acanthopanax species.1,3) Chiisanoside, the main terpenoid component of this plant, has been reported to have anti-hepatot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Nuclear factor-kB is a well-known mediator of inflammatory cytokines (Won et al, 2005), and it was shown to be activated during apoptosis following cell incubation with a variety of agents including VP-16 (Usami et al, 1998). Based on our previous and current observations, it seems plausible that MXF decreases VP-16-induced proinflammatory cytokine secretion in THP-1 cells via inhibition of NF-kB activation.…”
Section: Discussionmentioning
confidence: 59%
“…Nuclear factor-kB is a well-known mediator of inflammatory cytokines (Won et al, 2005), and it was shown to be activated during apoptosis following cell incubation with a variety of agents including VP-16 (Usami et al, 1998). Based on our previous and current observations, it seems plausible that MXF decreases VP-16-induced proinflammatory cytokine secretion in THP-1 cells via inhibition of NF-kB activation.…”
Section: Discussionmentioning
confidence: 59%
“…albeofructus inhibited the NO production and the iNOS expression through the down-regulation of NF-B binding activity in RAW264.7 macrophage cells. It has also been reported that syringaresinol, an active component of Acanthopanax senticosus, suppressed various inflammatory gene expression through inhibiting NF-B activity in SW982 human synovial sarcoma cell line (Won et al, 2005). Considered together, it seems like that Acanthopanax senticosus has anti-inflammatory activity via inhibition of NF-B activation.…”
Section: Discussionmentioning
confidence: 92%
“…Lipopolysaccharide has been reported to up‐regulate the expression of inflammatory mediators such as IL‐1β, tumour necrosis factor‐α (TNFα), IL‐6, nerve growth factor (NGF), inducible nitric oxide synthase (iNOS) and cyclooxygenase 2 (COX2)/prostaglandin E 2 (PGE 2 ) in RAW264.7 macrophages 11–13 . The nuclear factor‐κB (NF‐κB) signalling pathway is involved in LPS‐induced production of inflammatory mediators in this cell line 12,14 .…”
Section: Introductionmentioning
confidence: 99%